المقاربة النسوية للعلاقات الدولية - محمد الطاهر, عديلة (revue mofakir, 2018)
‫‪‫‪This‬‬ ‫‪article‬‬ ‫‪try‬‬ ‫‪to‬‬ ‫‪show,‬‬ ‫‪as‬‬ ‫‪detailed‬‬ ‫‪phase,‬‬ ‫‪a‬‬ ‫‪Theoritical‬‬ ‫‪Contribution‬‬ ‫‪of‬‬ ‫‪Feminist‬‬ ‫‪Approaches‬‬ ‫‪of‬‬ ‫‪International‬‬ ‫‪Relations,‬‬ ‫‪where‬‬ ‫‪accounts‬‬ ‫‪that‬‬ ‫‪the‬‬ ‫‪Academic‬‬ ‫‪Field‬‬ ‫‪of‬‬ ‫‪international‬‬ ‫‪relations‬‬ ‫‪is‬‬ ‫‪under‬‬ ‫‪Domination‬‬ ‫‪by‬‬ ‫‪Androcentrism,‬‬ ‫‪which‬‬ ‫‪exclude‬‬ ‫‪views‬‬ ‫‪of‬‬ ‫‪women,‬‬ ‫‪through‬‬ ‫‪many‬‬ ‫‪concepts‬‬ ‫‪as‬‬ ‫‪State,‬‬ ‫‪Power,‬‬ ‫‪Security,‬‬ ‫...‪Rationalism,‬‬ ‫‪which‬‬ ‫‪holds‬‬ ‫‪pure‬‬ ‫‪manhood‬‬ ‫‪attributes.‬‬